Prevalence of Physical Activity and Sedentary Behavior Patterns in Generally Healthy European Adults Aged 70 Years and Older—Baseline Results From the DO-HEALTH Clinical Trial - Mattle, Michèle; Meyer, Ursina; Lang, Wei; Mantegazza, Noemi; Gagesch, Michael; Mansky, Richard; Kressig, Reto W.; Egli, Andreas; Orav, E. John; Bischoff-Ferrari, Heike A. (Frontiers in Public Health, 2022)
Background Physical activity (PA) is important for healthy aging and disease prevention whereas sedentary behavior (SB) accelerates health deterioration. Aim To investigate activity profiles regarding PA and SB among generally healthy European older adults. Methods Meeting PA recommendations was defined as ≥150 min/week of moderate and/or ≥75 min/week of vigorous PA. A cut-off of ≥5.5 h/day was used to define time spent with SB. We present prevalence of PA and SB overall and by sex, age, BMI, and country. We examined correlates with multivariate logistic regression models. Results Two thousand one hundred and fifty-five DO-HEALTH participants completed baseline information on activity profiles [mean age 74.9 years (SD 4.5), 61.8% women]. Overall, 62.2% met PA recommendations and overall, 37.1% spent ≥5.5 h/day with SB. Younger participants (70–74 years), men, and those with BMI <25 kg/m2 met PA recommendations more often. Per country, prevalence of meeting PA recommendations were: Austria 74.4%, France 51.0%, Germany 65.6%, Portugal 46.5%, and Switzerland 66.7%. Regarding SB, prevalence did not differ in all subgroups. In multivariate logistic regression analyses, being male, younger age, lower MoCA scores, and higher SPPB score were associated with greater odds, whereas higher BMI, more years of education, higher GDS score, and residing in Portugal were associated with lower odds of meeting PA recommendations. High BMI and higher MoCA scores were associated with greater odds of high SB. Conclusion Individualized public health efforts may be warranted even in active older adults, as profiles were less favorable in subgroups of older age, female sex and higher BMI.